(untitled) (Pragyajyoti, 2021)
The study aims to explore the Contribution of remittance on economic progress of Dharan -6, Panmari. For this purpose, Twenty-five households having immigrant family members were selected in Dharan -6, Panmari. The information was collected through interview by using structured interview by using structured interviewed schedule. Descriptive statistics is carried out to analyze the Contribution of remittance on economic status of the sampled household in the past-migration period is better than that in the pre-migration period. In the study area, remittance is a main source of income. So, it has brought a qualitative change in economic status of migrant household. An improvement in the economic status of migrant household, the involvement of the household in community development activities and participation in social organization have brought a positive change in the overall socio economic status of the migrant household.